Harmonic Subtangent Structures - Adara M. Blaga (Journal of Mathematics)
The concept of harmonic subtangent structures on almost subtangent metric manifolds is introduced and a Bochner-type formula is proved for this case. Conditions for a subtangent harmonic structure to be preserved by harmonic maps are also given.